Excessively High Repair Tension Decreases Microvascular Blood Flow Within the Rotator Cuff. Issue 13 (November 2022) - Miyake, Satoshi; Izaki, Teruaki; Arashiro, Yasuhara; Kobayashi, Shunsuke; Shibata, Yozo; Shibata, Terufumi; Yamamoto, Takuaki
Background: Repair tension and microvascular blood flow within the rotator cuff has a critical impact on tendon healing after rotator cuff repair. However, the relationship between repair tension and microvascular blood flow within the rotator cuff remains unclear. Purpose/Hypothesis: The purpose of this study was to determine how much tension adversely affects microvascular blood flow within the rotator cuff. The hypothesis was that as the repair tension increases, the microvascular blood flow within the rotator cuff decreases. Study Design: Controlled laboratory study. Methods: Repair tension and microvascular blood flow within the rotator cuff of 30 patients with full-thickness rotator cuff tears were simultaneously measured using a digital tension meter and a contact-type laser Doppler flowmeter, respectively. Microvascular blood flow was measured under 4 levels of tension (0, 10, 20, and 30 N) at 5 points on the rotator cuff. The obtained values were statistically analyzed by a linear mixed-effects model to clarify the effect of tension on microvascular blood flow within the rotator cuff. Results: There was no statistically significant difference in microvascular blood flow (mL/min/100 g) within the rotator cuff between 0 N (mean, 3.51; 95% CI, 3.0-4.0) and 10 N (mean, 3.74; 95% CI, 3.2-4.3) of tension ( P = .716). However, there were statistically significant differences in microvascular blood flow within the rotator cuff between 0 and 20 N of tension (mean, 2.84; 95% CI, 2.3-3.4) ( P = .002) and between 0 and 30 N of tension (mean, 2.45; 95% CI, 1.9-3.0) ( P < .001). Conclusion/Clinical Relevance: Our findings indicate that tension of ≥10 N during rotator cuff repair significantly decreases the microvascular blood flow within the rotator cuff. These data will contribute to determining the optimal repair tension during rotator cuff repair.